2018
DOI: 10.14423/smj.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Geographic Variation and Sociodemographic Correlates of Hysterectomy Rates Among Reproductive-Age Women

Abstract: Objective For decades hysterectomy rates have famously demonstrated unexplained geographic variation. The aim of this study was to identify county-level correlates of hysterectomy rates among reproductive aged women. Methods Using county-level data from multiple sources, linked with claims-based surveillance data of every hysterectomy performed among women ages 18 to 44 in North Carolina from 2011 to 2013 (N=7,180), we explored social, economic, and healthcare factors associated with county-level rates. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
4
13
0
Order By: Relevance
“…First, our results demonstrate that women aged 15+ living in a municipality with lower 'Health and care' scores were more likely to undergo hysterectomies than those living in a municipality with a higher score. The positive and significant impact of 'Health and care' on municipal hysterectomy incidence is consistent with most literature findings (9,17,22). The score used for the variable included, among other factors, accesses to hospital or community health center.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…First, our results demonstrate that women aged 15+ living in a municipality with lower 'Health and care' scores were more likely to undergo hysterectomies than those living in a municipality with a higher score. The positive and significant impact of 'Health and care' on municipal hysterectomy incidence is consistent with most literature findings (9,17,22). The score used for the variable included, among other factors, accesses to hospital or community health center.…”
Section: Discussionsupporting
confidence: 85%
“…Women aged 15+ living in municipalities with lower 'Income and purchasing power' scores were less likely to receive hysterectomies. This association contradicts studies conducted in Belgium in the past decades (1,9) and other countries indicating that women with lower socioeconomic statuses are more likely to undergo hysterectomies (16,21,22). By contrast, a study in Finland found a positive association between disposable family income and hysterectomy rates (2), which was confirmed in two other studies on elective surgeries in the same country (34,35).…”
Section: Discussionmentioning
confidence: 88%
“…County-level associations between hysterectomy rate and race, independent of health care access, illustrate continued relevance of Jim Crow laws for gynecologic health. 33 Black women—especially those in the U.S. South—remain at higher risk of premenopausal hysterectomy. 34 Higher rates of hysterectomy is concerning in its own right, and may also limit community knowledge necessary to self-assess symptoms of gynecologic cancer, such as bleeding after menopause.…”
Section: Resultsmentioning
confidence: 99%
“…Some counties within both high‐ and low‐rate clusters are considered medically underserved, 47 underscoring the notion that health care availability is not necessarily a major factor in determining an area's hysterectomy rate. While literature on this topic is sparse, a recent NC‐based study demonstrated that socio‐demographic characteristics (eg, percent married and median household income) were strongly related to county‐level hysterectomy rates, while health care availability (eg, number of OB/GYNs) was not 48 . Local medical culture, however, may also influence treatment with hysterectomy 49 .…”
Section: Discussionmentioning
confidence: 99%